Technology - Polinchok, David (Henry Stewart Talks, 2009)
Customer service and customer retention, Captivating brand experiences, The experience of shopping, Shopping is not about stores, it's about stories, Today's consumers are looking to savor time, 'No risk', Brand experience philosophy, Innovation thinking, The marketplace as we know it, Advertising vs. experience, Positive brand experience, Today's consumer, Retail opportunities in a world of extremes, BEL guiding principles, Brand experience design, Emerging technology, Mixed and augmented reality